Sugar-energy/Sugarcane Expansion and Concentration of Agricultural Land in the state of São Paulo, Brazil, between 1996 and 2017 - Baccarin, José Giacomo [UNESP] (FapUNIFESP (SciELO), 2024)
The objective was to analyze the effects of sugar-energy/sugarcane expansion and other facts on the distribution of agricultural land tenure in the state of São Paulo, between 1996 and 2017. Through the literature review, reasons and trends of concentration of land tenure in world and Brazilian agriculture were systematized. From the recent evolution of the sugar-energy structure in São Paulo, factors with probable impacts on land distribution were addressed: area advance and deepening of sugarcane mechanization and continuity of high vertical integration between agroindustry and sugarcane production. In the empirical analysis, IBGE’s agricultural censuses and INCRA’s register of rural properties were used. The sugarcane expansion over other activities contributed significantly to the increase in the concentration of land ownership in São Paulo. This expansion took place, predominantly, through leasing and not the purchase of land. Thus, the concentrationist impact was smaller on property than on land tenure. The deepening of sugarcane mechanization also had a concentrationist effect, through the differentiation of companies. Small and medium-sized sugarcane suppliers, due to their insufficient area, tended to be excluded or incorporated by larger ones. The same occurred with some mills and large suppliers, which registered operational problems and increased indebtedness in accelerating sugarcane mechanization.
Expansão sucroenergética/canavieira e concentração da terra agrícola no estado de São Paulo, Brasil, entre 1996 e 2017
Keywords: agricultural mechanization; concentração econômica; distribuição da terra; economic concentration; land distribution; mecanização agrícola